Face (Mianzi) in academic settings : its relations with socially oriented achievement goals and self-esteem. - Lenny. (2010)
The present study sought to achieve a better understanding of ‘face’ (mianzi) construct in academic settings. First, it was by examining the relationship between ‘face’ (mianzi) and Socially Oriented Achievement Goals (SOAG). Literature findings have consistently shown that ‘face’ has an influence on individuals’ behaviors. In this study, we were to extend the findings by investigating if ‘face’ (mianzi) as a Chinese culture value would also be related to the endorsement of goals, particularly endorsement of social goals (SOAG). In addition, ‘face’ (mianzi) and self-esteem relationship was also examined to find out whether ‘face’ (mianzi) was a psychologically adaptive cultural value with regard to self-esteem. It was found that ‘face’ (mianzi) was significantly correlated with SOAG. Face-loss dimension of ‘face’ (mianzi) had a significant negative association with self-esteem.